Bottom depth carving the pelagic spatial organisation in large marine ecosystem: The case of North West Africa - Anne Mouget; Patrice Brehmer; Mohamed Ahmed Jeyid; Yannick Perrot; Ndague Diogoul; Momodou Sidibeh; Kamel Mamza; Anthony Acou; Abdoulaye Sarré (Continental Shelf Research, 2025)

Species identification of fish shoals using coupled split-beam and multibeam echosounders and two scuba-diving observational methods - Viviane David; Anne Mouget; Pierre Thiriet; Corentin Minart; Yannick Perrot; Loïc Le Goff; Olivier Bianchimani; Solène Basthard-Bogain; Tristan Estaque; Justine Richaume; Jean-François Sys; Adrien Cheminée; et al. (Journal of Marine Systems, 2024)

Applying Acoustic Scattering Layer Descriptors to Depict Mid-Trophic Pelagic Organisation: The Case of Atlantic African Large Marine Ecosystems Continental Shelf - Anne Mouget; Patrice Brehmer; Yannick Perrot; Uatjavi Uanivi; Ndague Diogoul; Salahedine El Ayoubi; Mohamed Ahmed Jeyid; Abdoulaye Sarré; Nolwenn Béhagle; Aka Marcel Kouassi; Eric Feunteun (Fishes, 2022)
To identify key nonspecific organisational characteristics of the mid-trophic pelagic communities, which remain a challenge, we work with sound scattering layers (SSLs). Application was tested in the three African Atlantic Large Marine Ecosystems (AALMEs) to assess the utility of adapting and developing new acoustic variables. Our methodology allowed comparison between Large Marine Ecosystems (LMEs) based on 14 morphological, spatial and acoustic variables to characterize SSLs over time. These original variables were effective in monitoring and comparing the LMEs, and even allowed us to discriminate different organisations inside the Canary Current LME. Common traits identified for all AALMEs included the importance of the shallowest SSL. However, we identified an unexpected night-time pattern in SSL distributions in the Benguela Current LME which reflect a major difference in diel vertical migration mechanisms relative to other AALMEs. We also highlighted the predominance of elementary sampling unit (ESUs) with a single SSL and an unoccupied tiny layer close to the bottom, even if some ESUs presented up to six SSLs. Inter-annual changes in SSL organisation are highlighted by adaptation of original variables as the proportion of the water column occupied by SSLs and the relative importance of the shallowest SSL. SSL variables have been used mostly in deep water; here, we applied them on the continental shelf. SSL variables can be used to standardize the monitoring of marine ecosystems and capture change in spatial structure and function of mid-trophic pelagic marine ecosystems worldwide, even in data-poor areas where species identification of lower-trophic pelagic organism remains a challenge.

Fine-scale vertical structure of sound-scattering layers over an east border upwelling system and its relationship to pelagic habitat characteristics - Ndague Diogoul; Patrice Brehmer; Yannick Perrot; Maik Tiedemann; Abou Thiam; Salaheddine El Ayoubi; Anne Mouget; Chloé Migayrou; Oumar Sadio; Abdoulaye Sarré (Ocean Science, 2020)
Understanding the relationship between sound-scattering layers (SSLs) and pelagic habitat characteristics is a substantial step to apprehend ecosystem dynamics. SSLs are detected on echo sounders representing aggregated marine pelagic organisms. In this study, SSL characteristics of zooplankton and micronekton were identified during an upwelling event in two contrasting areas of the Senegalese continental shelf. Here a cold upwelling-influenced inshore area was sharply separated by a strong thermal boundary from a deeper, warmer, stratified offshore area. Mean SSL thickness and SSL vertical depth increased with the shelf depth. The thickest and deepest SSLs were observed in the offshore part of the shelf. Hence, zooplankton and micronekton seem to occur more frequently in stratified water conditions rather than in fresh upwelled water. Diel vertical and horizontal migrations of SSLs were observed in the study area. Diel period and physicochemical water characteristics influenced SSL depth and SSL thickness. Although chlorophyll-a concentration insignificantly affected SSL characteristics, the peak of chlorophyll a was always located above or in the middle of the SSLs, regularly matching with the peak of SSL biomass. Such observations indicate trophic relationships, suggesting SSLs to be mainly composed of phytoplanktivorous zooplankton and micronekton. Despite local hypoxia, below 30 m depth, distribution patterns of SSLs indicate no vertical migration boundary. The results increase the understanding of the spatial organization of mid-trophic species and migration patterns of zooplankton and micronekton, and they will also improve dispersal models for organisms in upwelling regions.

Study of tribological behaviour of fresh mortar against a rigid plane wall - Yannick Mélinge; Viet Hai Hoang; Damien Rangeard; Arnaud Perrot; Christophe Lanos (European Journal of Environmental and Civil Engineering, 2013)